Anger and physical activity. A study in college students - Galdón-López, S.; Fernández-García-Valdecasas, B.; Álvarez-Ferrándiz, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Physical activity is of vital importance in these times where uncertainty and desperation abound. It has become the solution given that knowing its benefits and being constant the proposed goals can be achieved. For these reasons, the following objectives were set: to analyse the level of physical activity and anger and to establish the possible relationships between general, academic, psychosocial and physical-sports variables in university students, with a total sample of 497 university students aged between 18 and 51 years. Various instruments have been used to achieve the objectives such as an ad-hoc questionnaire for the socio-demographic variables. On the other hand, the attitude scale towards physical activity and the Aggressiveness Questionnaire, for the psychosocial variables. The results show how doing physical activity on a daily basis and having a good attitude towards it reduces aggressive behaviour in university students and, thus reduces their irascibility.